Pengaruh Likuiditas, Kecukupan Modal, dan Efisiensi Operasional terhadap Kinerja Keuangan Bank Perekonomian Rakyat Konvensional Di Kabupaten Badung - Maharani, Ni Komang Ayu; Purnamawati, I Gusti Ayu (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to ascertain and test empirically the influence of Liquidity (LDR), Capital Adequacy (CAR), and Operational Efficiency (BOPO) on the Financial Performance (ROA) of Conventional Rural Bank in Badung Regency. This research employs a quantitative approach using secondary data from banking financial reports for the period ending December 31 on the website www.ojk.go.id during 2021-2023. The study’s population consisted of all 47 conventional rural banks in Badung Regency, and purposive sampling was the method employed for sampling. The samples used that met the criteria in this study were 28 conventional rural banks. The data analysis technique used was multiple linear regression analysis with IBM SPSS Statistic version 30 software. The result showed that (1) liquidity has an impact on the financial performance of conventional rural bank in Badung Regency for the period 2021-2023, (2) capital adequacy has an impact on the financial performance of conventional rural bank in Badung Regency for the period 2021-2023, (3) operational efficiency has an impact on the financial performance of conventional rural bank in Badung Regency for the period 2021-2023.